Konseling Pastoral Terhadap Perempuan Korban Kekerasan Seksual - Gratia Thalia Siwi (PT. Giat Konseling Nusantara, 2025)
Sexual violence against women is an act which presents gender issues that result in suffering for women in terms of physical, psychological, mental, and social including the threats to these actions, enforcement or what is called deprivation of liberty, whether it occurs in public or individual life privately. Therefore, the purpose of this research is to describe how important pastoral counseling services are for women victims of sexual violence to restore the lives of victims holistically. The method used is descriptive qualitative research, all data were collected through observation and interviews so that the results of this study indicate that pastoral counseling services are the only successful way to recover victims of sexual violence in all aspects of their lives.